Energy Markets in Latin America : Emerging Disruptions and the Next Frontier - World Bank (World Bank, Washington, DC, 2018)
Efficient energy services are essential for economic growth, competitiveness, and human development. Globally, energy markets are undergoing a transformation: fossil fuel prices are responding to new and unpredictable dynamics, and new energy and information and communication technologies (ICT) are emerging and disrupting traditional market architectures. The 2030 development agenda for sustainable development adopted in September 2015 by the 193 countries of the United Nations General Assembly establishes sustainable energy as number seven of its 17 sustainable development goals (SDG7). It seeks to ensure access to affordable, reliable, sustainable, and modern energy for all. While much of the finance will have to come from the private sector, public finance - both national budgets and concessional transfers - will have a crucial role to play in helping set economies on the right path. So in this increasingly complex and rapidly changing context, how are Latin America and Caribbean (LAC) energy markets progressing? How will emerging disruptions and game changers influence the evolution and transformation of energy markets in LAC? How ready are existing markets and institutions to actively move toward the next frontiers of efficiency? What is needed to break through to the modern, efficient, secure, and sustainable energy systems needed to support the regional economy in the coming years? What investment will be needed and how is LAC poised to attract private finance? This report explores these questions and offers insights into paths and indicative actions needed to approach the next efficiency frontier. The report focuses on electricity and gas markets. The analysis acknowledges the varying conditions and challenges of different countries in the region. Intraregional variation is addressed through analysis of country groupings and selection of appropriate comparators, benchmarks, and best practice frontiers.